1997
DOI: 10.1046/j.1365-2249.1997.4431456.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthase (NOS) aggravates Staphylococcus aureus septicaemia and septic arthritis

Abstract: SUMMARYThe aim of this study was to assess the role of NO and its metabolites in bacterial arthritis. The murine model of haematogenously acquired septic arthritis was used. Swiss mice treated with NOS inhibitors (N G -monomethyl-L-arginine or N q -nitro-L-arginine methyl ester) were injected intravenously with toxic shock syndrome toxin-1 (TSST-1) producing Staphylococcus aureus LS-1. Arthritis was evaluated clinically and histopathologically. Serum cytokine levels, bacterial isolates and intracellular capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…1D). In addition to cytokines, we also looked at the induction of nitric oxide (NO) which has been shown to play a role in killing of S. aureus in mice (19, 20). Previous work has indicated that for optimal NO production BMDM need to be primed with IFN-γ (21), so we assessed NO in BMDM that were either unprimed or primed with IFN-γ for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…1D). In addition to cytokines, we also looked at the induction of nitric oxide (NO) which has been shown to play a role in killing of S. aureus in mice (19, 20). Previous work has indicated that for optimal NO production BMDM need to be primed with IFN-γ (21), so we assessed NO in BMDM that were either unprimed or primed with IFN-γ for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…aureus effectively triggers PHOX activity (73) and, depending on the context, is a potent inducer of NOS2 (17). In vivo, mice deficient for either PHOX or NOS2 have an increased susceptibility to S. aureus infections (52,69,70). Macrophages from mice with an individual knockout of the PHOX or NOS2 gene showed an unaltered ability to kill S. aureus in vitro compared to WT M (42), whereas neutrophils from PHOX-deficient mice were ineffective in killing S. aureus (23,34,62).…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in iNOS show increased susceptibility to L. monocytogenes (20,38). iNOS deficiency is also associated with increased mortality from S. aureus infection (39,40). However, the biology of NO is complicated.…”
Section: Discussionmentioning
confidence: 99%